Potential Role of Vδ2+ γδ T Cells in Regulation of Immune Activation in Primary HIV Infection - Bhatnagar, Nupur; Girard, Pierre-Marie; Lopez-Gonzalez, Moises; Didier, Céline; Collias, Lio; Jung, Corinne; Bollens, Diane; Duvivier, Claudine; Von Platen, Cassandre; Scott-Algara, Daniel; Weiss, Laurence; , for the ANRS EP-56 Group; et al. (Frontiers in Immunology, 2017)
Although conventional Tregs are sufficient in controlling low residual T-cell activation in ART-treated patients, they are not efficient in controlling exaggerated immune activation associated with high levels of HIV replication in primary HIV infection (PHI). Our previous data suggested that double negative (DN) T cells including mainly gd DN T cells play a role in the control of immune activation in PHI. Since gd T cells are capable of exerting regulatory functions, we investigated their implication as regulatory T cells in PHI as well as chronic HIV infection (CHI). In a cross-sectional study of 58 HIV-infected patients, in the primary and the chronic phase either ART-treated or untreated, we analysed phenotype and cytokine production of gd T cells using flow cytometry. Cytokine production was assessed following in vitro stimulation with IPP or plate-bound anti-CD3/anti-CD28 MAbs. We found that the proportion of gamma delta T cells negatively correlated with CD8 T-cell activation in PHI patients. Further, we found that in these patients, the Vd2 receptor bearing (Vd2+) gd T cells were strongly activated, exhibited low terminal differentiation, and produced the anti-inflammatory cytokine, TGF-b. In contrast, in untreated-CHI we observed a remarkable expansion of gd T cells, where the Vd2+gd T cells comprised of an elevated proportion of terminally differentiated cells producing high levels of IFN-g but very low levels of TGF-b. We also found that this loss of regulatory feature of gd T cells in CHI was a lasting impairment as we did not find recovery of TGF-b production even in ART-CHI patients successfully treated for more than 5 years. Our data therefore suggests that during the primary phase of HIV infection, Vd2+gd T cells may act as regulatory T cells controlling immune activation through production of TGF-b. However in CHI, gd T cells transform from an anti-inflammatory into pro-inflammatory cytokine profile and participate in sustenance of immune activation.